Strategi Dakwah Ustadz Muslim Siregar Upaya Meningkatkan Pengetahuan Dan Pengalaman Ibadah Shalat - Nur Oktari; Khairuddin (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
The main problem of this research is how the strategy used by Ustadz Muslim Siregar in Efforts to Build Application Data and Practices in the City of Gunung Tua Tumbu Jati. The problem in this proposition is to look at the method used by Ustadz Muslim Siregar With the Final Purpose of Growing Data and Application Practices for the Environment of Gunung Tua Tumbu Jati City. The type of investigation used by the maker is field research with an expressive abstract philosophy, the data grouping used is affirmation, collection, and documentation. The result of the assessment is Ustadz Muslim Siregar's Dakwah, explicitly by moving recitations where Ustadz Muslim Siregar uses 3 philosophies of da'wah namely Wise methodology (Al-manhaj-'athifi) offering direction in a sensitive way, a wise framework (Al-Manhaj Al-' Aqli) giving questions and answers to people who really don't sort out the material presented, material strategy (Al-manhaj al-'alhissi) by giving examples in daily attendance, for example coming to the mosque before starting the recitation time, welcoming neighbors ask, study dhikr.